The project manager : mastering the art of delivery - Newton, Richard, 1964- (Financial Times/Prentice Hall, 2005)
Learn how to be the safe pair of hands in your organisation, consistently delivering exceptional projects on time and to budget. The steep rise in demand for good project managers in recent years has been mirrored by the publication of book after book setting out the formal processes and mechanics of project management. Whether they are textbooks or books aimed at the practitioner, they all usually cover the same ground - the ABCs of project management, you might call it. But anyone who has ever managed a project or overseen the management of a project in the real world knows that there is a significant difference between mastering the ABCs and mastering the practice of project management itself. It's not that the formal methodologies don't work, but rather that it's only half of the picture. To go from good to great in project management, you need to shift your focus back to the real basics of management. In this illuminating book, Richard Newton, a successful project manager with twenty years' experience, will show you several ways you can elevate your game. Topics covered include: What is successful delivery? Communications - learning to understand who the customers are, what they want, and how best to communicate with them What actually is your project? Understanding the importance of scope and how best to define it How to get your project started Optimal personal styles for project managers Managing your project Getting the best out of your project team A quick survey of the most important tools and techniques When to constructively kill a project Whether you are just starting out in project management, or have a few years under your belt and want to achieve real mastery, The Project Manager will deliver.